PRICING ON LOW-LIQUIDITY EXCHANGES, PROBLEMS AND SOLUTIONS - Liudmyla Boldyrieva; Vitaliy Kustov (Izdevnieciba "Baltija Publishing", 2021)
This article examines the technology of futures supply, which includes three directions in its structure: trading, clearing (clearing organization, position calculations), supply process (non-deliverable contracts, deliveries of goods at a specific elevator, electronic warehouse document management, electronic digital signature system). The schemes of application of futures instruments at grain elevators have been singled out. It was found out that the domestic system of grain accounting at grain elevators loses much in comparison with the system of custodial (depositary) accounting, in centralization, in the presence of unified rules, as well as in other parameters. It is proposed to use market makers to provide a continuous flow of exchange liquidity (that is, to provide liquidity to both buyers and sellers at the same time). Methodology. The scientific research is based on the developments of domestic and foreign economists, as well as own observations and conclusions. Results. It turned out that, in theory, every trader can become a market maker by placing a pending limit order in the trading blotter. Specific examples are given, with figures, of how exactly the same product can be traded on a low-liquid and a high-liquid exchange. Three scenarios are proposed and it is concluded that the probability of the third scenario is quite high. Practical implications. It is proved that the Last Look system is one of the methods for solving the problem of market maker risk. It is shown that the main data transfer protocols between the exchange and its institutional participants can be Fix and Fast Data Protocols. The advantages and disadvantages of Fix and Fast data protocols are highlighted. It was found that the Fast protocol is actively implemented on trading floors, but it is still inferior in prevalence to the "classic" protocol Fix. Value/originality. Ensure the use of futures instruments in elevators. It is proposed to use market makers to provide a continuous flow of exchange liquidity.